Synthetic fluorescent MYC probe: Inhibitor binding site elucidation and development of a high-throughput screening assay. (15th July 2021) - Shirey, Ryan J.; Hart, Jonathan R.; Sridharan, BanuPriya; Novick, Scott J.; Turner, Lewis D.; Zhou, Bin; Nielsen, Alexander L.; Eubanks, Lisa M.; Ueno, Lynn; Hixon, Mark S.; Lairson, Luke L.; Spicer, Timothy P.; et al.
Graphical abstract: Abstract: We report the discovery of a fluorescent small molecule probe. This probe exhibits an emission increase in the presence of the oncoprotein MYC that can be attenuated by a competing inhibitor. Hydrogen–deuterium exchange mass spectrometry analysis, rationalized by induced-fit docking, suggests it binds to the "coiled-coil" region of the leucine zipper domain. Point mutations of this site produced functional MYC constructs resistant to inhibition in an oncogenic transformation assay by compounds that displace the probe. Utilizing this probe, we have developed a high-throughput assay to identify MYC inhibitor scaffolds. Screening of a diversity library (N = 1408, 384-well) and a library of pharmacologically active compounds (N = 1280, 1536-well) yielded molecules with greater drug-like properties than the probe. One lead is a potent inhibitor of oncogenic transformation and is specific for MYC relative to resistant mutants and transformation-inducing oncogenes. This method is simple, inexpensive, and does not require protein modification, DNA binding, or the dimer partner MAX. This assay presents an opportunity for MYC inhibition researchers to discover unique scaffolds.